REPRESENTASI PEMIKIRAN MARXISME DALAM FILM BIOGRAFI STUDI SEMIOTIKA JOHN FISKE MENGENAI PERTENTANGAN KELAS SOSIAL KARL MARX PADA FILM GURU BANGSA TJOKROAMINOTO - Aisyah Nurul Kusumastuti; Catur Nugroho (SEMIOTIKA: Jurnal Komunikasi, 2017)
Film is an audio-visual language that always record the reality that grows and develops in the community, and then project it on the big screen. The film Guru Bangsa Tjokoraminoto is a biopic which tells the history of Tjokroaminoto’s struggle to against the Dutch government’s policy and to eliminate social inequality inside the society at that time. In this film tucks into a Marxist ideology that not all of the audience will aware of it. Therefore, researchers are interested to analyze the representation of this ideology in the film. The study, entitles "Representation of Marxism on Guru Bangsa Tjokroaminoto’s Film (Study of John Fiske Semiotics about Karl Marx Social Class Conflict)" aim to determine how the representation of the ideology of Marxism, particularly the opposition social class through the elements of the costumes and dialogue. The focus of this research is how the representation of social class conflict through the elements of cinematic mise en scene from it’s costumes and sound elements in the form of dialogue. By using descriptive qualitative method with analytic theory of semiotics John Fiske, has obtained the results of research that there is representation of the Marxism ideology, particularly the opposition social class display of differences in the costumes worn on the players that has its own meaning, as well as the dialogues that emphasize their social class conflict.Keywords: Representation, Marxism, Film, Semiotics, Social Class